Infrastructure expenditure policy and private sector output in Nigeria 1970-1998 - Central Bank of Nigeria (Abuja, Nigeria 1999, 1999)
Infrastructure expenditure policy is crucial in accessing the state of infrastructure in any economy. In Nigeria the provision of almost all types of infrastructure has been the responsibility of government. This study situates the problem of infrastructure in Nigeria in two broad perspective, the investment in infrastructure and the priorities of funding as we move into the millennium and second, the impact of public physical capital on private sector output.
A study by the research department and international economic relations department, central bank of Nigeria. November 20, 1999.
nmn, 11/08/16
Loan
Keywords: Public utilities, Financial aspects; Infrastruture; Private sector output; Infrastructure expenditure policy; Nigeria